Perovskite precursor solution, perovskite composite film solution and preparation method and application thereof
By using technical means such as macromolecular polymers and titanium acetylacetonate ligands, the problem of instability of perovskite nanomaterials in humid environments is solved, the stability and photoelectric properties of perovskite composite films are improved, and the efficient photoelectric conversion effect is achieved.
Patent Information
- Application Number
- CN202510003613.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Existing perovskite nanomaterials are unstable in humid environments, resulting in ion migration and exciton non-radiative recombination, reducing photoluminescence efficiency and photoelectric properties. At the same time, the thermal injection synthesis is difficult to control the reaction temperature, affecting product quality.
The polymerization of macromolecular polymer 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane is carried out to form a perovskite precursor solution, and the stability and photoelectric properties of the perovskite composite film are improved by coating the titanium acetylacetonate ligand and ethylene-vinyl acetate copolymer.
It improves the purity and stability of perovskite CsPbX3, enhances the photoelectric conversion efficiency, filling factor and stability of solar cells, and maintains long-term stability in humid environments and high temperatures.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectric conversion technology, and in particular to a perovskite precursor solution, a perovskite composite thin film solution, and a preparation method and application thereof. Background Art
[0002] Perovskite materials (lead cesium chloride) have high photoluminescence quantum yield (PLQY), tunable wavelength, wide absorption range and unique quantum confinement effect. They have made great achievements in the field of optoelectronics and are favored by experts and scholars in the fields of solar cells, LED displays, photodetectors, gas sensors, etc. Perovskite nanocrystals have certain ionic crystal properties, which makes them easily ionized and undergo phase transitions in water or polar solvents, so they cannot exist for a long time in a humid environment. Ion migration will lead to ion vacancies, increase the non-radiative recombination of excitons, and thus reduce the photoluminescence efficiency and optoelectronic performance.
[0003] There are many methods for synthesizing perovskite nanomaterials, including ultrasound, microwave, solvent thermal, hot injection, etc., mainly hot injection. However, hot injection has the following defects: on the one hand, since high temperature hot injection requires a higher temperature during the reaction process, and it is difficult to control the reaction temperature during the fast injection and fast cooling reaction process, it is difficult to synthesize the ideal product; on the other hand, when synthesizing perovskite quantum dots, octadecene and octadecene are usually used as surface ligands to change their shape and size, but these commonly used ligands are bound to the surface of perovskite quantum dots in a long chain, and the bonds formed are extremely unstable, so the stability of all-inorganic perovskite quantum dots has not been guaranteed.
[0004] In practical applications, factors such as perovskite and surface ligands are of great significance to improve device performance. The photoluminescence (PL) intensity of CsPbBr3 can be improved by passivating surface defects such as cation or anion vacancy differences. For example, by doping perovskite NCs with polymers, organic ligands, and inorganic ions (Yb 3+ , Sr 2+ , Mn 2+ The PLQY and stability can be greatly improved. In addition, the prior art discloses encapsulating the perovskite precursor in a polymethyl methacrylate fiber membrane to improve the stability of the perovskite composite film, and embedding the perovskite precursor in polystyrene microspheres to prepare a stable fluorescent sensor. However, the above methods have the disadvantages of being relatively expensive and time-consuming.
[0005] Therefore, it is of great significance to study and obtain a perovskite precursor solution and a perovskite composite thin film solution that can improve the stability and photoelectric conversion efficiency of optoelectronic devices. Summary of the invention
[0006] The purpose of the present invention is to provide a perovskite precursor solution, a perovskite composite film solution and a preparation method and application thereof in view of the deficiencies in the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a perovskite precursor solution, comprising the following steps:
[0009] 1) PbX2, octadecene and oleylamine are mixed to obtain a mixed solution; a macromolecular polymer is added to the mixed solution to obtain a lead precursor solution;
[0010] 2) mixing cesium acetate, octadecene and oleic acid to obtain a cesium precursor solution;
[0011] 3) mixing the cesium precursor solution and the lead precursor solution and cooling with ice water to obtain a perovskite precursor solution;
[0012] The perovskite precursor is CsPbX3, and X in PbX2 and CsPbX3 is I, Br or Cl.
[0013] Preferably, the macromolecular polymer is obtained by polymerization reaction of 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 2,2-bis(3-amino-4-hydroxyphenyl) hexafluoropropane.
[0014] Preferably, in the mixed solution of step 1), the molar concentration of PbX2 is 0.05-0.15 mol / L, the volume ratio of octadecene and oleylamine is 10-15:1-3; the mass ratio of the macromolecular polymer and PbX2 is 0.02-0.1:100.
[0015] Preferably, in the cesium precursor solution of step 2), the molar concentration of cesium acetate is 0.05-0.15 mol / L, the volume ratio of octadecene to oleic acid is 8-10:1; the molar ratio of cesium acetate to PbX2 of step 1) is 3:4-6.
[0016] Preferably, the mixing in steps 1) and 2) is carried out under a nitrogen atmosphere, the mixing time in step 3) is 10 to 20 seconds, and the mixing temperature is 130 to 150°C.
[0017] The present invention also provides a perovskite precursor solution prepared by the preparation method.
[0018] The present invention also provides a method for preparing a perovskite composite thin film solution from the perovskite precursor solution, comprising the following steps:
[0019] The perovskite precursor solution and the titanium acetylacetonate solution are mixed and then added into a toluene solution of ethylene-vinyl acetate copolymer to obtain a perovskite composite film solution.
[0020] The present invention also provides a perovskite composite thin film solution prepared by the method for preparing a perovskite composite thin film solution from a perovskite precursor solution.
[0021] The present invention also provides the use of the perovskite precursor solution or the perovskite composite film solution in a photoelectric device.
[0022] The beneficial effects of the present invention include the following:
[0023] 1) The present invention obtains a macromolecular polymer by polymerizing 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane. The macromolecular polymer contains a large number of carbonyl groups and trifluoromethyl groups, which can provide sufficient lone pair electrons to react with Pb 2+ The unfilled p orbital of Pb 2+ The energy barrier defects left on the surface of the perovskite layer reduce the non-radiative recombination at the perovskite interface and grain boundary, promote the longitudinal transfer of charges, and increase the purity of the perovskite CsPbX3 to more than 99.99%. The perovskite precursor has a cubic perovskite structure, which improves the stability of the perovskite, thereby improving the photoelectric conversion efficiency, filling factor and stability of solar cells.
[0024] 2) The present invention adopts titanium acetylacetonate ligand to improve the stability of perovskite. When exposed to air, the surface Ti-based ligand is oxidized to TiO2, which is used to encapsulate perovskite crystals; ethylene-vinyl acetate copolymer (EVA) is used to coat the perovskite crystals, and the obtained perovskite composite film has good regularity, excellent waterproofness and flexibility, which improves the stability and optical properties of the perovskite composite film in a humid environment, and further improves the photoelectric conversion efficiency of photovoltaic devices such as solar cells.
[0025] 3) The perovskite composite film binds the lead ions in the perovskite through the interaction between EVA and perovskite, and prevents them from interacting with environmental water molecules, thereby improving the carrier mobility, improving the photoelectric properties of the perovskite composite film, and extending the material life; the EVA coating and the bonding of the macromolecular polymer to the lead ions make the perovskite composite film have long-term stability in air and water and at high temperatures, and the photoelectric performance is significantly improved. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing a perovskite precursor solution, comprising the following steps:
[0027] 1) PbX2, octadecene and oleylamine are mixed to obtain a mixed solution; a macromolecular polymer is added to the mixed solution to obtain a lead precursor solution;
[0028] 2) mixing cesium acetate, octadecene and oleic acid to obtain a cesium precursor solution;
[0029] 3) mixing the cesium precursor solution and the lead precursor solution and cooling with ice water to obtain a perovskite precursor solution;
[0030] The perovskite precursor is CsPbX3, and X in PbX2 and CsPbX3 is I, Br or Cl.
[0031] In the present invention, the macromolecular polymer is preferably obtained by polymerization of 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 2,2-bis(3-amino-4-hydroxyphenyl) hexafluoropropane.
[0032] In the present invention, the preparation method of the macromolecular polymer is: 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 2,2-bis(3-amino-4-hydroxyphenyl) hexafluoropropane and a solvent are mixed and then subjected to polymerization reaction to obtain the macromolecular polymer. The molar volume ratio of 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 2,2-bis(3-amino-4-hydroxyphenyl) hexafluoropropane and the solvent is preferably 1-1.5 mol: 1-1.5 mol: 30-50 mL, more preferably 1-1.2 mol: 1-1.2 mol: 35-45 mL, more preferably 1.2 mol: 1.2 mol: 36-40 mL; the polymerization reaction time is preferably 8-10 h, more preferably 8.5-9.5 h, more preferably 9 h, the polymerization reaction temperature is preferably 30-50 ° C, more preferably 35-45 ° C, more preferably 40 ° C, and the polymerization reaction is carried out under stirring conditions.
[0033] In the present invention, in the mixed solution of step 1), the molar concentration of PbX2 is preferably 0.05-0.15 mol / L, more preferably 0.08-0.12 mol / L, and more preferably 0.1 mol / L. The volume ratio of octadecene and oleylamine is preferably 10-15:1-3, more preferably 11-14:1.5-2.5, and more preferably 12-13:2; the mass ratio of the macromolecular polymer and PbX2 is preferably 0.02-0.1:100, more preferably 0.04-0.08:100, and more preferably 0.05-0.06:100.
[0034] In the present invention, in the cesium precursor solution of step 2), the molar concentration of cesium acetate is preferably 0.05-0.15 mol / L, more preferably 0.08-0.12 mol / L, and more preferably 0.1 mol / L. The volume ratio of octadecene and oleic acid is preferably 8-10:1, and more preferably 9:1; the molar ratio of cesium acetate and PbX2 in step 1) is preferably 3:4-6, more preferably 3:4.5-5.5, and more preferably 3:5.
[0035] In the present invention, the mixing in steps 1) and 2) is preferably carried out under a nitrogen atmosphere, the mixing time in step 3) is preferably 10 to 20 seconds, more preferably 12 to 18 seconds, more preferably 14 to 15 seconds, and the mixing temperature is preferably 130 to 150°C, more preferably 135 to 145°C, more preferably 140°C.
[0036] The present invention also provides a perovskite precursor solution prepared by the preparation method.
[0037] The present invention also provides a method for preparing a perovskite composite thin film solution from the perovskite precursor solution, comprising the following steps:
[0038] The perovskite precursor solution and the titanium acetylacetonate solution are mixed and then added into a toluene solution of ethylene-vinyl acetate copolymer to obtain a perovskite composite film solution.
[0039] In the present invention, ethylene-vinyl acetate copolymer is ultrasonically dispersed in toluene, and a mixed solution of a perovskite precursor solution and a titanium acetylacetonate solution is added under stirring to obtain a perovskite composite thin film solution; the volume ratio of the perovskite precursor solution to the titanium acetylacetonate solution is preferably 1:3-5, more preferably 1:3.5-4.5, and more preferably 1:4, and the concentration of the titanium acetylacetonate solution is preferably 4-7 mg / L, and more preferably 5-6 mg / L; the volume ratio of the perovskite precursor solution to toluene is preferably 2-60 μL:1 mL, more preferably 10-40 μL:1 mL, and more preferably 20-30 μL:1 mL; the mass volume ratio of ethylene-vinyl acetate copolymer to toluene is preferably 0.05-0.15 g:1 mL, more preferably 0.06-0.12 g:1 mL, and more preferably 0.08-0.1 g:1 mL.
[0040] The present invention also provides a perovskite composite thin film solution prepared by the method for preparing a perovskite composite thin film solution from a perovskite precursor solution.
[0041] The present invention also provides the use of the perovskite precursor solution or the perovskite composite film solution in a photoelectric device.
[0042] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0043] In the embodiment, the preparation method of the macromolecular polymer is as follows: 1 mol of 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 1 mol of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane are added to 30 mL of N,N-dimethylformamide, and a polymerization reaction is carried out at 40° C. and a rotation speed of 500 r / min for 9 hours. After the polymerization reaction is completed, deionized water is added to precipitate a solid, which is then filtered and dried to obtain a macromolecular polymer.
[0044] Example 1
[0045] In a nitrogen atmosphere, lead bromide, octadecene and oleylamine are mixed to obtain a mixed solution, in which the concentration of lead bromide is 0.1 mol / L, and the volume ratio of octadecene to oleylamine is 12:2; a macromolecular polymer is added to the mixed solution to obtain a lead precursor solution, and the mass ratio of the macromolecular polymer to lead bromide is 0.05: 100. In a nitrogen atmosphere, cesium acetate, octadecene and oleic acid are mixed to obtain a cesium precursor solution, in which the concentration of cesium acetate is 0.1 mol / L, and the volume ratio of octadecene to oleic acid is 9:1.
[0046] The cesium precursor solution was quickly added to the lead precursor solution (the molar ratio of cesium acetate and lead bromide was 3:5) at 140° C., mixed for 12 seconds, and then cooled with ice water to obtain a perovskite precursor (CsPbBr3) solution.
[0047] After mixing a perovskite precursor solution and an acetylacetonate titanium aqueous solution (in the acetylacetonate titanium aqueous solution, the concentration of acetylacetonate titanium is 5 mg / L) in a volume ratio of 1:4, the mixed solution is added to a toluene solution of ethylene-vinyl acetate copolymer to obtain a perovskite composite thin film solution. The volume ratio of the perovskite precursor solution and toluene is 20 μL:1 mL, and the mass volume ratio of ethylene-vinyl acetate copolymer and toluene is 0.1 g:1 mL.
[0048] The purity of CsPbBr3 in the perovskite precursor solution of this embodiment is 99.995%.
[0049] Example 2
[0050] In a nitrogen atmosphere, lead iodide, octadecene and oleylamine were mixed to obtain a mixed solution, in which the concentration of lead iodide was 0.08 mol / L and the volume ratio of octadecene to oleylamine was 11:1.5; a macromolecular polymer was added to the mixed solution to obtain a lead precursor solution, in which the mass ratio of the macromolecular polymer to lead iodide was 0.06:100. In a nitrogen atmosphere, cesium acetate, octadecene and oleic acid were mixed to obtain a cesium precursor solution, in which the concentration of cesium acetate was 0.08 mol / L and the volume ratio of octadecene to oleic acid was 8:1.
[0051] The cesium precursor solution was quickly added to the lead precursor solution (the molar ratio of cesium acetate and lead iodide was 3:4.5) at 135° C., mixed for 10 seconds and then cooled with ice water to obtain a perovskite precursor (CsPbI3) solution.
[0052] After mixing a perovskite precursor solution and an acetylacetonate titanium aqueous solution (in the acetylacetonate titanium aqueous solution, the concentration of acetylacetonate titanium is 4 mg / L) in a volume ratio of 1:3, the mixed solution is added to a toluene solution of ethylene-vinyl acetate copolymer to obtain a perovskite composite thin film solution. The volume ratio of the perovskite precursor solution and toluene is 10 μL:1 mL, and the mass volume ratio of ethylene-vinyl acetate copolymer and toluene is 0.06 g:1 mL.
[0053] The purity of CsPbI3 in the perovskite precursor solution of this embodiment is 99.991%.
[0054] Example 3
[0055] In a nitrogen atmosphere, lead bromide, octadecene and oleylamine were mixed to obtain a mixed solution, in which the concentration of lead bromide was 0.12 mol / L, and the volume ratio of octadecene to oleylamine was 14:2.5; a macromolecular polymer was added to the mixed solution to obtain a lead precursor solution, and the mass ratio of the macromolecular polymer to lead bromide was 0.07:100. In a nitrogen atmosphere, cesium acetate, octadecene and oleic acid were mixed to obtain a cesium precursor solution, in which the concentration of cesium acetate was 0.12 mol / L, and the volume ratio of octadecene to oleic acid was 10:1.
[0056] The cesium precursor solution was quickly added to the lead precursor solution (the molar ratio of cesium acetate and lead bromide was 3:5.5) at 145° C., mixed for 15 seconds, and then cooled with ice water to obtain a perovskite precursor (CsPbBr3) solution.
[0057] After mixing a perovskite precursor solution and an acetylacetonate titanium aqueous solution (in the acetylacetonate titanium aqueous solution, the concentration of acetylacetonate titanium is 6 mg / L) in a volume ratio of 1:5, the mixed solution is added to a toluene solution of ethylene-vinyl acetate copolymer to obtain a perovskite composite thin film solution. The volume ratio of the perovskite precursor solution and toluene is 40 μL:1 mL, and the mass volume ratio of ethylene-vinyl acetate copolymer and toluene is 0.12 g:1 mL.
[0058] The purity of CsPbBr3 in the perovskite precursor solution of this embodiment is 99.993%.
[0059] Comparative Example 1
[0060] The macromolecular polymer in Example 1 was omitted, and other conditions were the same as in Example 1.
[0061] Comparative Example 2
[0062] The titanium acetylacetonate aqueous solution in Example 1 was omitted, the mass ratio of the macromolecular polymer to lead bromide was changed to 0.01:100, and the other conditions were the same as in Example 1.
[0063] The polymer perovskite solar cell was prepared using the perovskite composite film solution of Examples 1 to 3. The specific preparation process was as follows: ITO conductive glass was used as the substrate, and ultrasonically cleaned with acetone, isopropanol, deionized water, and alcohol for 15 minutes, then dried with nitrogen, and quickly transferred to a glove box in a nitrogen atmosphere after ultraviolet ozone cleaning for 15 minutes. 20 μL of 3 mg / mL poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] was spin-coated on the surface of the conductive glass, and after the spin coating was completed, it was transferred to a 100°C heating table and heated for 10 minutes to obtain a hole transport layer. After the perovskite composite film solution (60 μL) of the embodiment and the comparative example was spin-coated on the surface of the hole transport layer, 30 μL of toluene was added dropwise, and then transferred to a 100°C heating table and heated for 10 minutes to obtain a perovskite composite film layer. 35μL of electron transport layer solution (23mg [6,6]-phenyl C61 butyric acid methyl ester dissolved in 1mL chlorobenzene) was spin-coated on the surface of the perovskite composite film layer, then transferred to a 100℃ heating table for heating for 10min, and then spin-coated with 45μL of 2.5mg / mL bathocuproin to obtain the electron transport layer. Finally, the substrate with the electron transport layer prepared was placed in a vacuum coating machine, evacuated to a vacuum degree of 100Pa, and a silver metal source was placed in a tungsten boat, and a silver metal electrode was evaporated to obtain a polymer perovskite solar cell. The performance of the polymer perovskite solar cell was tested.
[0064] The photoelectric conversion efficiency of the solar cells of Examples 1 to 3 are 27.5%, 27.3% and 26.9%, respectively, and the filling factors are 82.56%, 82.48% and 82.52%, respectively. The photoelectric conversion efficiency of the solar cells of Comparative Examples 1 and 2 are 20.56% and 21.18%, respectively, and the filling factors are 77.52% and 78.16%, respectively.
[0065] 30 μL of toluene was added to 60 μL of the perovskite composite film solutions of Examples 1 to 3 and Comparative Examples 1 to 2, respectively, and then transferred to a heating table at 100°C for heating for 10 minutes to obtain a perovskite composite film for stability testing. The specific process of the stability test is: the perovskite film is soaked in water and then dried, and its physical phase is measured by an X-ray diffractometer to observe whether the physical phase has changed. The results show that after the perovskite composite films of Examples 1 to 3 were soaked in water for 40 days, the phase of the composite film did not change significantly, and it had very high water stability; the perovskite film of Comparative Examples 1 to 2 changed significantly after being soaked in water for 20 days.
[0066] The perovskite composite thin film solutions of Examples 1 to 3 and Comparative Examples 1 to 2 were heated to 70°C and their morphological changes were observed. The results showed that the perovskite composite thin films of Examples 1 to 3 still maintained their original morphology after 200 min and had excellent high-temperature morphological stability. The morphology of the perovskite thin films of Comparative Examples 1 to 2 changed significantly after 130 min and 145 min, respectively.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a perovskite precursor solution, characterized in that: The following steps are included: 1) PbX2, octadecene and oleylamine are mixed to obtain a mixed solution; a macromolecular polymer is added to the mixed solution to obtain a lead precursor solution; 2) mixing cesium acetate, octadecene and oleic acid to obtain a cesium precursor solution; 3) mixing the cesium precursor solution and the lead precursor solution and cooling with ice water to obtain a perovskite precursor solution; The perovskite precursor is CsPbX3, and X in PbX2 and CsPbX3 is I, Br or Cl.
2. The preparation method according to claim 1, characterized in that: The macromolecular polymer is obtained by polymerization reaction of 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane.
3. The preparation method according to claim 1, characterized in that: In step 1), the molar concentration of PbX2 in the mixed solution is 0.05-0.15 mol / L, the volume ratio of octadecene to oleylamine is 10-15:1-3; and the mass ratio of the macromolecular polymer to PbX2 is 0.02-0.1:
100.
4. The preparation method according to claim 1 or 3, characterized in that: In the cesium precursor solution of step 2), the molar concentration of cesium acetate is 0.05-0.15 mol / L, the volume ratio of octadecene to oleic acid is 8-10:1; the molar ratio of cesium acetate to PbX2 of step 1) is 3:4-6.
5. The preparation method according to claim 4, characterized in that: The mixing in steps 1) and 2) is carried out under a nitrogen atmosphere, the mixing time in step 3) is 10 to 20 seconds, and the mixing temperature is 130 to 150°C.
6. The perovskite precursor solution prepared by the preparation method according to any one of claims 1 to 5.
7. The method for preparing a perovskite composite thin film solution from a perovskite precursor solution according to claim 6, characterized in that: The following steps are included: The perovskite precursor solution and the titanium acetylacetonate solution are mixed and then added into a toluene solution of ethylene-vinyl acetate copolymer to obtain a perovskite composite film solution.
8. The perovskite composite thin film solution prepared by the method for preparing a perovskite composite thin film solution from a perovskite precursor solution according to claim 7.
9. Use of the perovskite precursor solution according to claim 6 or the perovskite composite thin film solution according to claim 8 in a photoelectric device.
Citation Information
Patent Citations
Ethylene-vinyl acetate copolymer coated CsPbX3 nanocrystalline composite film
CN113817456A
Perovskite precursor material and preparation method and application thereof
CN115332449A
Perovskite solar cell and preparation method thereof
CN116209288A
KR20210004659A